2013
DOI: 10.7314/apjcp.2013.14.11.6541
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Apoptotic-inducing Effects of Purple Rice Extracts and Chemotherapeutic Drugs on Human Cancer Cell Lines

Abstract: Pigmented rice is mainly black, red, and dark purple, and contains a variety of flavones, tannin, polyphenols, sterols, tocopherols, γ-oryzanols, amino acids, and essential oils. The present study evaluated the cytotoxic effects of purple rice extracts (PREs) combined with chemotherapeutic drugs on human cancer cells and mechanisms of cell death. Methanolic (MeOH) and dichloromethane (DCM) extracts of three cultivars of purple rice in Thailand: Doisaket (DSK), Nan and Payao (PYO), were tested and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…Several investigations have demonstrated that pigmented rice extract exhibits antioxidant, antiinflammatory, and in vitro anticarcinogenic activities (Kong and Lee, 2010;Leardkamolkarn et al, 2010;Min et al, 2010). In addition, pigmented rice extract showed cytotoxic and apoptotic-inducing effects on human hepatocellular carcinoma HepG2 cells and also exhibited anti-metastasis activity against human breast cancer cells (Banjerdpongchai et al, 2013;Luo et al, 2014).…”
Section: Rawiwanmentioning
confidence: 99%
“…Several investigations have demonstrated that pigmented rice extract exhibits antioxidant, antiinflammatory, and in vitro anticarcinogenic activities (Kong and Lee, 2010;Leardkamolkarn et al, 2010;Min et al, 2010). In addition, pigmented rice extract showed cytotoxic and apoptotic-inducing effects on human hepatocellular carcinoma HepG2 cells and also exhibited anti-metastasis activity against human breast cancer cells (Banjerdpongchai et al, 2013;Luo et al, 2014).…”
Section: Rawiwanmentioning
confidence: 99%
“…Cytotoxicity of red rice extracts on HT1080 and MDA-MB-231 cells were determined by MTT assay as described previously (Banjerdpongchai et al, 2013). HT1080 and MDA-MB-231 cells were plated at 1.5x103 cells per well in 96-well plates and cultured in DMEM with 10% FBS.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Although the anticancer activities of purple rice have been reported in vitro and in vivo ( Wongjaikam et al, ), (Summart & Chewonarin, ), (Banjerdpongchai et al, ), its effects on prostate cancer have been less clearly demonstrated. The researchers therefore decided to determine the effect of PRE on the development of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, purple rice crude ethanolic extract (PRE) showed anticancer effects in both the pre‐ and post‐initiation stages of colon cancer (Wongjaikam, Summart, & Chewonarin, ), (Summart & Chewonarin, ). Furthermore, various strains of purple rice extract showed cytotoxic effects against human hepatocellular carcinoma (HepG2) and prostate cancer cells (LNCaP) (Banjerdpongchai, Wudtiwai, & Sringarm, ). This study therefore sought to investigate the effect of PRE on testosterone‐induced BPH in castrated rats, and explore the mechanisms of its action on the androgen‐responsive human prostate cancer cell line LNCaP and on bacterial mutagenicity.…”
Section: Introductionmentioning
confidence: 99%